Decoding brain activities of literary metaphor comprehension: An event-related potential and EEG spectral analysis - Sun, Lina; Chen, Hongjun; Zhang, Chi; Cong, Fengyu; Li, Xueyan; Hämäläinen, Timo (Frontiers in Psychology, 2022)
Literary metaphors are always conceived as more creative, novel, and open-ended in meaning. However, disagreement appears on how literary metaphors differ from metaphors elsewhere. Based on the arguments, this study intended to explore the neural mechanisms of literary metaphors from modern Chinese lyrics through the methods of Event-Related Potentials (ERPs) and Event-Related Spectral Perturbation (ERSPs), as compared to conventional metaphors and literal expressions outside literature. Forty-eight subjects were recruited and required to read to the prime-target pairs in three language conditions. Based on the ERPs results, the earliest differences were presented during the time window of P200 component (170~260ms) in the frontal and central areas, with the amplitude of P200 for literary metaphors more positive than the other two conditions, reflecting the early allocation of attention and the early conscious experience of the experimental stimuli. Meanwhile, significant differences were presented during the time window of N400 effect (430–530 ms), with the waveform of literary metaphors more negative than others in the frontal and central topography of scalp distributions, indicating more efforts in retrieving conceptual knowledge for literary metaphors. The ERSPs analysis revealed that the frequency bands of delta and theta were both involved in the cognitive process of literary metaphor comprehension, with delta band distributed in the frontal and central scalp and theta band in parietal and occipital electrodes. Increases in the two power bands during different time windows provided extra evidences that the processing of literary metaphors required more attention and effort than nonliterary metaphors and literal statements in the semantic related tasks, suggesting that the cognitive process of literary metaphors are distinguished by different EEG spectral patterns.